Pengaruh Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Aini, Zahratul; Lalu Hamdani Husnan, Lalu Hamdani Husnan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to determine the Effect of Capital Structure and Profitability on Company Value in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange for the 2020-2022 Period. This research is associative using quantitative data. The sampling technique used is purposive sampling and data collection techniques, namely documentation. The number of samples used in this study was 36 companies. The analysis method used in this study is multiple linear regression analysis using eviews 12. The results of this study show that capital structure (DER) has a negative insignificant effect on company value. And profitability (ROE) has a positive insignificant effect on the value of the company.